Evaluation of Ozone Formation Potential of Formaldehyde Using Smog Chamber Data - Hailiang Zhang; Yongfu Xu; Long Jia (Aerosol and Air Quality Research, 2023)
Abstract Formaldehyde (HCHO) is one of the important O3 precursors in the atmospheric environment, but the mechanism for HCHO photochemical reactions is not very clear now. In the present study, the effects of relative humidity (RH) and initial VOC/NOx ratio (RCN) on the HCHO-NOx photochemical reaction process are studied in terms of smog chamber experiments. The MCM mechanism of formaldehyde is evaluated based on the experimental results. The measured maximum ozone concentration (O3-max) increases first and then decreases with the increase of RCN, and the RCN at the inflection point is 4.0 and 4.8 in the low (RH = 7.8%‒11.5%) and high RH (RH = 71.9%‒84.0%) experiments, respectively. The RH has no obvious effect on the measured O3-max values. The original MCM simulated O3 concentration reaches the maximum value much earlier than the experimental result, but can well simulate the incremental reactivity (IR) values in the experiments. The simulated incremental reactivity of HCHO at 6 h (IR6h) by MCM is influenced by other VOCs, and the simulated maximum IR6h is 1.9 ppb ppb−1, demonstrating that the contribution of HCHO to ozone is comparable to that of acetaldehyde in the atmospheric environment.